2019
DOI: 10.1016/j.jep.2019.111844
|View full text |Cite
|
Sign up to set email alerts
|

Natural dietary antioxidants containing flavonoids modulate keratinocytes physiology: In vitro tri-culture models

Abstract: ETHNOPHARMACOLOGICAL RELEVANCE: Several traditional medicinal herbs are widely used for dermatologic and cosmetic preparations. The beneficial skin repair activity is detected in various phases of wound-healing process, such as cell-cell, cell-matrix interactions or collagen synthesis. AIM OF THE STUDY: The study assessed the effects of Opuntia ficus-indica (L.) Mill. (Opuntia) and Milk Thistle (MT) (Silybum marianum (L.) Gaerth) on adult keratinocytes (HaCaT) functioning under basal condition or in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…BC promoted endothelial proliferation, while VSD and MXD enhanced angiogenic potential. Moreover, only HSP increased VEGFR-2 phosphorylation [31].…”
Section: Natural Alternative Interventionsmentioning
confidence: 92%
“…BC promoted endothelial proliferation, while VSD and MXD enhanced angiogenic potential. Moreover, only HSP increased VEGFR-2 phosphorylation [31].…”
Section: Natural Alternative Interventionsmentioning
confidence: 92%
“…In addition, we attempted to unravel the molecular features beyond this beneficial effect, and we evaluated the key biomarkers that involved in the tissue repair. Recently, Bassino and collaborators [18] found that plant extracts modulated MMPs expression by using scratched HaCaT cells in an in vitro model. In fact, that natural compounds that contained flavonoids changed the MMP-9 expression at all doses tested, though only during wound repair, and were not modulated in physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In short, HDF were seeded in 48-well plate for 3 days prior to additional seed of HaCaT cells seeded onto the HDF and further incubated for 24 h. Thereafter, the cocultures were treated with the samples, i.e., AE1, AE3, AE24, verbascoside and dexamethasone (D4902, Sigma, UK), incubated for 24 h, exposed with UV (UV lamp, Cole-Parmer, USA), i.e., UVA for 15 min (1 J/cm 2 ) and UVB for 25 s (30 mJ/cm 2 ), incubated for 24 h. Cell viability (%) was monitored with CellTiter-Glo luminance (Promega, USA). Cellular activity of the samples against MMP-9 (ab100610, Abcam, UK) in the coculture system was examined at the noncytotoxic concentrations (150 µg/mL for AE1, AE3, AE24 and verbascoside, 10 µg/mL for dexametasone) in a comparison with the control groups, i.e., vehicle control with UV exposures and vehicle non-UV control 29 .…”
Section: Methodsmentioning
confidence: 99%